Physical Characteristics of Yellow Coloured Jelly Available in Indian Market and Mineral Contents Therein - Rane, R.A.; Mehta, B.H. (Asian Journal of Chemistry, 2010)
Yellow coloured jellies of different forms and brands were analyzed for their physical characteristics such as pH, loss on drying, ash, degree brix, refractive index, acidity calculated as citric acid and content of tannin. The mineral contents such as Fe, Cu, Zn, Sn, Pb, Cr and Cd were analysed by atomic absorption spectrophotometer (AAS). Sn and Cr were found to be below detectable level and Cd was found to be less than 0.007 mg/100 g. All other elements were present in variable concentration at ppm level.